Efficacy Of Vitamin E For Alleviating The Symptoms Of Primary Dysmenorrhea: A Review Of Randomized Clinical Trials And Quasi Experimental Studies (Journal of Pharmaceutical Negative Results, 2023)
Myometrial contractions generated by prostaglandins cause primary dysmenorrhea. The uterine ischemia and sensitivity of afferent nerve fibres to painful stimuli are additional effects of prostaglandins. Nonsteroidal anti-inflammatories are useful medications, however some women should not take them and many women only see a slight improvement in their symptoms. Prostaglandin synthesis inhibitors, or NSAIDs (like Ibuprofen), work well for treating primary dysmenorrhea, although they may not be appropriate for people who have stomach ulcers or bronchospastic hypersensitivity to aspirin. Nausea, dyspepsia, diarrhoea, and occasionally exhaustion are moderate side effects that can occur. Today, vitamins are crucial in the management of dysmenorrhea. Primary dysmenorrhea is relieved by vitamin E, and its antioxidant properties may also prevent arachidonic acid from being oxidised, which would reduce the amount of prostaglandin produced. The safety of vitamin E supplementation, especially in large doses, has been questioned. People who use blood thinners or have a vitamin K deficiency may have a higher risk of bleeding. When used in healthy adults at dosages typically found in food and in healthy people over 65 at doses up to 800 IU taken orally daily for up to four months, vitamin E is probably safe. This brief review aims to demonstrate Vitamin E's effectiveness in treating primary dysmenorrhea.